The prevalence and causes of hyperglycemia in newborns - Sen, Yasar; Kurt, Nese; Dogan, Yasar; Akarsu, Saadet; Aygun, Denizmen (Aves, 2008)
Aim: The prospective study was performed to determine the prevalence and risk factors of hyperglycemia to newborns admitted in the neonatal unit. Material and Method: The newborns that had blood glucose levels > 150 mg/dl and referred to the Neonatal Unite, Medical Center of Firat University, between January 1 - July 1, 2007 were enrolled in the study. Prenatal, natal, and postnatal histories, examination and laboratory findings, glucose infusion rates, other diseases diagnosed and, treatments received, duration of hyperglycemia, and prognosis of newborns with hyperglycemia were assessed. Results: The prevalence of neonatal hyperglycemia was 2.9% during the study period. Its prevalence rates were 4.5%, 5.2%, 6.5%, 13.9%, and 30.8%, respectively in newborns receiving parenteral glucose infusion, preterm, low birthweight, very low birthweight, and extremely low birthweight infants. The mean diagnosis age, mean gestational age, and mean birth weight of those hyperglycemic neonates were 4.3 +/- 4.1 days, 33.2 +/- 5.1 weeks and 2248.46 +/- 1450.62 g, respectively. The mean blood glucose level and mean intravenous glucose rate at the time of diagnosis was 398.53 +/- 170 mg/dl, and 4.8 +/- 2.0 mg/kg/min, respectively. The mean duration of hyperglycemia was 15.8 +/- 10.8 hours. The most important risk factors associated with neonatal hyperglycemia were maturity, birth asphyxia, respiratory distress syndrome and sepsis, respectively. Conclusions: Hyperglycemia has become a significant risk factor for morbidity and mortality during the neonatal period. The prevalence of hyperglycemia increases in newborn babies, as the birthweight and gestational age of neonates decrease. Blood glucose levels should be monitored daily in all infants who receive intravenous glucose infusions until blood glucose concentration becomes stable.
Yenido?anlarda hiperglisemi sikli?i ve nedenleri
Keywords: Hyperglycemia; newborn; premature; small gestational age